2019
DOI: 10.31234/osf.io/9c2e5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recognition of identity and expressions as integrated processes

Abstract: According to the dominant account of face processing, recognition of emotional expressions is implemented by the superior temporal sulcus (STS), while recognition of face identity is implemented by inferior temporal cortex (IT) (Haxby et al., 2000). However, recent patient and imaging studies (Fox et al., 2011, Anzellotti et al. 2017) found that the STS also encodes information about identity.Jointly representing expression and identity might be computationally advantageous: learning to recognize expressions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…1C). The results indicated that the expression-selective units spontaneously emerged in the VGG-Face pretrained for face identity recognition, which echoed previous findings (19,20).…”
Section: Expression-selective Units Spontaneously Emerge In the Pretr...supporting
confidence: 86%
See 1 more Smart Citation
“…1C). The results indicated that the expression-selective units spontaneously emerged in the VGG-Face pretrained for face identity recognition, which echoed previous findings (19,20).…”
Section: Expression-selective Units Spontaneously Emerge In the Pretr...supporting
confidence: 86%
“…Thus, DCNNs could be a useful model simulating the processes of biological neural systems. More recently, several seminal studies have found that the DCNNs trained to recognize facial expression spontaneously developed facial identity recognition ability, and vice versa, suggesting that integrated representations of identity and expression may arise naturally within neural networks like humans do (19,20). However, a recent study found that face identity-selective units could spontaneously emerge in an untrained DCNN (21), which seemed to cast substantial doubt on the role of nurture in developing face perception and the abovementioned speculation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hyperparameter optimization via the CNN-GA approach offers promising prospects for improving model capabilities in increasingly complex recognition tasks in the future. Tang's network structure 71.2 [37] Caffe-imageNet 65.5 [22] MNF CNN+L2 SVM 70.3 [38] Raspberry Pi 65.97 [39] DenseNet 63.50 [40] VGG16 69.40 [41] Attention CNN 70.02 [42] ResNet with gate implementation 71.80 [43] VGGNet 73.28 [44] VGG progressive SpinalNet 74.39 VGG SpinalNet 74.45 [45] Mini-Xception 66.00 [46] CNN with transfer learning 72.00 [47] CNN with HOG feature 75.…”
Section: Resultsmentioning
confidence: 99%